Karakterisasi Zat Warna Tomat (Solanum lycopersicum) FRAKSI Metanol:N-Heksan Sebagai Photosensitizer Pada Dye Sensitized Solar Cell (DSSC) - Wahab, Nur Hasbi; Aisyah, Aisyah Aisyah; Suriani, Suriani (Al-Kimia, 2016)
One of the potential alternative energy to be developed to overcome energy crisis in the world is an DSSC. This research aimed to make a series of Dye Sensitized Solar Cell (DSSC) using an organic dye from crude extract of tomato as a photosensitizer. The dye obtained from the maceration by of ultrasonic waves using methanol. Separation was done by KKCV using eluent of methanol: n-hexane (3: 7, 1: 1, 7: 3). The best efficiency value (Ƞ) in the series of DSSC that results from the fraction methanol: n-hexane (1:1) was 0.0249%. Characterization using spectrophotometer UV-Vis showed a maximum absorption at wavelength of 447 nm which is the absorption of carotene compound. FTIR analysis showed that samples generally have -CH2-, C=C and OH strecth wich are the characteristic of carotene compound. GCMS analysis showed that dye components which estimated is dihydroxy lycopene of the retention time 10.93 with a molecular ion peak at m/z 91.